Phylogenetic analysis of HPAI H5N1 virus from duck swab specimens in Indonesia - Mutisari, Dewi; Muflihanah, Muflihanah; Wibawa, Hendra; Hendrawati, Ferra; Putra, Hamdu Hamjaya; Sulistyo, Kartika Priscillia; Ahmad, Ahyar; Sjahril, Rizalinda; Mubin, Risna Halim; Sari, Dwi Kesuma; Massi, Muhammad Nasrum (Journal of Advanced Veterinary and Animal Research, 2021)
Objective: A phylogenetic study was carried out on the avian influenza virus (AIV) isolated from a disease outbreak in Sidenreng Rappang Regency, South Sulawesi, Indonesia, in 2018. Material and Methods: Oropharyngeal swabs and organ samples were obtained from ducks that showed clinical symptoms: torticollis, fascial edema, neurological disorders, the corneas appear cloudy, and death occurs less than 1 day after symptoms appear. In this study, isolate A/duck/ Sidenreng Rappang/07180110-11/2018 from duck was sequenced and characterized. Results: It was found that each gene segment of the virus has the highest nucleotide homology to the Indonesian highly pathogenic avian influenza (HPAI) H5N1 clade 2.3.2.1c. Multiple alignments of the sample Hemagglutinin (HA) gene with the avian influenza references virus showed that the pattern of amino acid arrangement in the cleavage site PQRERRRK-RGLF is the characteristic of the HPAI virus. In addition, the HA gene contained Q222 (glutamine) and G224 (glycine), signifying a high affinity to avian receptor binding specificity (SA α2,3 Gal). Furthermore, there was no genetic reassortment of this virus based on the phylogenetic analysis of HA, NA, PB1, PB2, PA, NP, M, and NS genes. Conclusion: The HPAI H5N1 clade 2.3.2.1c virus was identified in duck farms in South Sulawesi, Indonesia. J. Adv. Vet. Anim. Res., 8(2): 346-354, June 2021